Screening of boron adsorption potential of various date seed preparation methods - Ahmed, Moussa Mohamed; Jami, Mohammed Saedi; Salleh, Md Noor; Mirghani, Mohamed Elwathig Saeed (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Recently boron has been classified as a pollutant of drinking water in many countries. Boron is harmful to many plants especially sensible plants and human health. Therefore, boron level needs to be decreased to 0.3 mg/l for drinking water and from 0.5 mg/l to 1 mg/l for irrigation water. In this study, various operational parameters are tested in order to determine feasibility of using date seed (or date pit or date stone) to remove boron from seawater. The objective of this study is to determine boron adsorption potentials of various date seed preparation methods (i.e., powdered, activated, acid treated and oil extracted seed) by batch adsorption process using synthetic boron contaminated water. All seeds were washed with distilled water and dried at 105°C for 24 hours. Then it was crushed using mortar and particle size of 106 m was selected for this study. Nevertheless, the raw date seeds were kept without any treatment and then the carbonised date seeds were burnt at 500°C for 1 hour in the furnace and the Soxhlet was used so that to achieve oil extraction. The last type of adsorbent which is acid treated date seed was achieved by treating the thermally activated date seed with 1 mol/l of HCl at room temperature for 8 hours. Therefore acid treated stone were filtered, washed with pure water and dried 100 °C for 12 hours and sieved again at 106 m.The results showed that the acid treated date seed is the best in terms of boron removal at pH 7 in 2 hours of reaction time and liquid solid ratio of 5. Indeed, the acid-treated date seed has removed 89.18% of boron and followed by oil extracted seed which has removed 88.105% boron, then activated date seed has removed 73.56% of boron and the last is the raw date seed which has removed 64.93% of boron.